Impact of Benign Prostatic Hyperplasia Pharmacological Treatment on Transrectal Prostate Biopsy Adverse Effects - Marina Zamuner; Ciro Eduardo Falcone; Arnaldo Amstalden Neto; Tomás Bernardo Costa Moretti; Luis Alberto Magna; Fernandes Denardi; Leonardo Oliveira Reis (Advances in Urology)
Background. Benign prostatic hyperplasia (BPH) pharmacological treatment may promote a decrease in prostate vascularization and bladder neck relaxation with theoretical improvement in prostate biopsy morbidity, though never explored in the literature. Methods. Among 242 consecutive unselected patients who underwent prostate biopsy, after excluding those with history of prostate biopsy/surgery or using medications not for BPH, we studied 190 patients. On the 15th day after procedure patients were questioned about symptoms lasting over a week and classified according to pharmacological BPH treatment. Results. Thirty-three patients (17%) were using alpha-blocker exclusively, five (3%) 5-alpha-reductase inhibitor exclusively, twelve (6%) patients used both medications, and 140 (74%) patients used none. There was no difference in regard to age among groups (P=0.5). Postbiopsy adverse effects occurred as follows: hematuria 96 (50%), hematospermia 53 (28%), hematochezia 22 (12%), urethrorrhagia 19 (10%), fever 5 (3%), and pain 20 (10%). There was a significant negative correlation between postbiopsy hematuria and BPH pharmacological treatment with stronger correlation for combined use of 5-alpha-reductase inhibitor and alpha-blocker over 6 months (P=0.0027). Conclusion. BPH pharmacological treatment, mainly combined for at least 6 months seems to protect against prostate biopsy adverse effects. Future studies are necessary to confirm our novel results.